MAPPING THE SUITABILITY OF ECOLOGICAL AND SOCIAL CONDITIONS OF Rafflesia patma IN PANGANDARAN NATURE RESERVE - Ibnu Mustofa; Lies Rahayu Wijayanti Faida; Denni Susanto (Universitas Gorontalo, 2021)
Rafflesia patma is one of endangered species in Indonesia. It is nature population was currently decreasing due to Rafflesia patma holoparasitic nature, whose existence depends on its host (Tetrastigma sp). Pangandaran Nature Reserve is one of areas which has become the habitat of Rafflesia patma in Indonesia. This study aimed to know the suitability of ecological and social habitat for Rafflesia patma in Pangandaran Nature Reserve. The Spatial Multi Criteria Analysis (SMCA) had been done using ecological and social conditions approach that influencing the existence of Rafflesia patma. Parameters of ecological conditions used were the presence of Rafflesia patma, host, predators, and water source. While the social conditions used were the center of human activity and accessibility. Each parameter was scored and overlaid into a map of the suitability of ecological and social conditions. Scoring in each parameter based on a literature study. The result showed that there were three classes of suitability for ecological and social conditions. Location with the most suitable result was 52,5 ha or 12,52%, suitable 176,5 ha 42,09%, and that did not suitable for the ecological and social conditions was 190,3 ha or 45,39%. Location with the most suitable conditions for Rafflesia patma habitat spread in the area which was an ecotone of coastal forest and lowland forest. Based on these results, the management of Pangandaran Nature Reserve need to pay more attention to the ecological habitat of Rafflesia patma. In addition, restrictions on community activities also need to be carried out in order to minimize habitat disturbance by the surrounding community.